2010
DOI: 10.3168/jds.2009-2301
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of progesterone via controlled internal drug release inserts during ovulation synchronization protocols in lactating dairy cows

Abstract: Our objective was to determine the effect of exogenous progesterone (P4) during a timed artificial insemination (TAI) protocol on pregnancies per AI (P/AI) in dairy cows not previously detected in estrus. Lactating cows (n=3,248) from 7 commercial dairy herds were submitted to a presynchronization protocol (2 injections of PGF(2alpha) 14 d apart; Presynch), and cows in estrus after the second PGF(2alpha) received AI (EDAI; n=1,583). Cows not inseminated by 12 to 14 d after the second PGF(2alpha) injection were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
5
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 22 publications
8
52
5
10
Order By: Relevance
“…The improvement in the pregnancy-30 and 70 rates (around 10% and 5%; respectively) after incorporating a new CIDR into the Ovsnch protocol (New-CIDRsynch) is in agreement with previous studies incorporated the CIDR into the Ovsynch (Stevenson et al, 2006;Stevenson et al, 2008;Colazo et al, 2013) Presynch (Melendez et al, 2006;Chebel at al., 2010) or Cosynch (Stevenson et al, 2003) but in disagreement with other reports incorporated the CIDR into Presynch (Bartolome et al, 2009;Colazo et al, 2013) or Ovsynch (Rivera et al, 2005;Mendonçaa et al, 2012). The improvement occurred after incorporating the CIDR in to Ovsynch was explained by higher ability to induce estrous in non-cyclic cows (Stevenson et al, 2003;Cerri et al, 2009) or improving the fertility of cows which did not have a CL at the beginning of the protocol (Stevenson et al, 2008) or cows showed an early luteolysis before administration of PGF2α (Stevenson et al, 2006).…”
Section: Reused-cidrsynchsupporting
confidence: 77%
See 3 more Smart Citations
“…The improvement in the pregnancy-30 and 70 rates (around 10% and 5%; respectively) after incorporating a new CIDR into the Ovsnch protocol (New-CIDRsynch) is in agreement with previous studies incorporated the CIDR into the Ovsynch (Stevenson et al, 2006;Stevenson et al, 2008;Colazo et al, 2013) Presynch (Melendez et al, 2006;Chebel at al., 2010) or Cosynch (Stevenson et al, 2003) but in disagreement with other reports incorporated the CIDR into Presynch (Bartolome et al, 2009;Colazo et al, 2013) or Ovsynch (Rivera et al, 2005;Mendonçaa et al, 2012). The improvement occurred after incorporating the CIDR in to Ovsynch was explained by higher ability to induce estrous in non-cyclic cows (Stevenson et al, 2003;Cerri et al, 2009) or improving the fertility of cows which did not have a CL at the beginning of the protocol (Stevenson et al, 2008) or cows showed an early luteolysis before administration of PGF2α (Stevenson et al, 2006).…”
Section: Reused-cidrsynchsupporting
confidence: 77%
“…These results are in agreement with previous results in cows with unknown cyclicity status (Galvão et al, 2004;Stevenson et al, 2006), cows with no CL at the beginning of the protocol (Stevenson et al, 2006;Stevenson et al, 2008), cyclic or anovulatory cows (Galvão et al, 2004). Otherwise they are in disagreement with other reports on cows with different cyclicity status (Bartolome et al, 2009), cows with no CL or anovulatroy cows (Stevenson et al, 2006;Chebel et al, 2010). The cyclicity status of the cow greatly affected the embryonic loss after the GnRH-based synchronization protocol and the embryonic loss in noncycling cows was twice that in cycling cows (Galvão et al, 2004;Stevenson et al, 2006).…”
Section: Reused-cidrsynchcontrasting
confidence: 50%
See 2 more Smart Citations
“…Similarly, concentrations of P4 on the day of PGF2α-induced luteolysis had a positive linear correlation with subsequent fertility (Diskin et al, 2006). More recent manipulative studies have shown some improvements (~5% to 7% increase in percentage pregnant) by using a controlled internal drug release (CIDR; releases P4) during the Ovsynch program before AI (Stevenson et al, 2006 andChebel et al, 2010;Bilby et al, 2013). Nevertheless, the results from these studies may not be due exclusively to the elevation in P4 produced by the CIDR, because improvements in synchronization may also accompany the use of a CIDR in the Ovsynch protocol.…”
Section: Fertility In Dairy Cowsmentioning
confidence: 97%